Pendayagunaan Filantropi Islam dan Warning Signals Terhadap Potensi Fraud - Nanang Setiawan (IQTISHODUNA, 2023)
This research aims to explore the empowerment of Islamic philanthropy and provide warning signal recommendations for preventing fraud risk. This research is qualitative, using the desk study method, and presents data on ten Islamic philanthrophy. This research uses two methods as warning signals against fraud risk: the Allocation to Collection Ratio (ACR) and the Amil Rights Ratio (RHA). The results show that through the ACR method, Badan Amil Zakat Nasional (BAZNAS), Lazis Muhammadiyah (Lazismu), Dompet Dhuafa (DD), Baitul Maal Muamalat (BMM) and Inisiatif Zakat Indonesia (IZI) have a higher potential for fraud based on cash balances that settle above 10%. As for the RHA method, Rumah Zakat (RZ), with an RHA of 13.8%, has a higher potential for fraud based on the more dominant orientation of institutional interests. This research contributes to additional literacy regarding empowering funds for Islamic philanthropic institutions and provides a warning signal as a prevention of fraud risk so that it can effectively minimize fraud./em>